MULTICULTURAL EDUCATION BUILDS TOLERANCE IN ELEMENTARY SCHOOLS - Andini Putri Endria; Mery Nurkhaliza; Sherli Chaca Oktavia; Yakub Simamora (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Lampung, 2026)
Multicultural education is an important educational approach for preparing students to understand, appreciate, and respond positively to diversity within society. This study examines the role of multicultural education in fostering tolerant attitudes and strengthening students’ character at the elementary school level. In a culturally, ethnically, religiously, and socially diverse country such as Indonesia, the development of tolerance from an early age is essential for preventing prejudice, discrimination, and social conflict. Through multicultural education, students are encouraged to recognize and respect differences in ethnicity, religion, culture, language, traditions, and social backgrounds while developing an understanding of equality and mutual respect. Teachers play a significant role in implementing these values by creating an inclusive, democratic, safe, and supportive learning environment in which every student has equal opportunities to participate and express their perspectives. The implementation of multicultural values can be integrated into curriculum content, classroom activities, cooperative learning, school traditions, and students’ daily interactions. This study also identifies several factors that support and hinder the development of tolerant attitudes among elementary school students. Supporting factors include curriculum integration, teacher commitment and competence, inclusive school culture, learning resources, and family involvement. Meanwhile, limited teacher understanding, inadequate learning resources, differences in family backgrounds, and the persistence of stereotypes and prejudice may become challenges in implementation. The study concludes that effective multicultural education can contribute to the development of students who demonstrate tolerance, empathy, respect, openness, and responsibility toward others. Therefore, strengthening multicultural education at the elementary school level is essential for developing a generation capable of living harmoniously and constructively within a diverse society.